The Role of Biphosphonate and Denosumab in Bone Metastasis - Cahyanur, Rahmat; Pravita, Aravinda (http://dharmais.co.id/, 2024)
Metastasis is a major contributor to cancer-related morbidity and mortality. Bone metastasis is prevalent and associated with pain and fractures, particularly in breast cancer where up to 80% of patients may be affected. Bisphosphonates, traditional anti-resorptive drugs, have been crucial in managing bone metastatic cancers. This article reviews the pathophysiology of bone metastasis, focusing on the invasion-metastasis cascade and the role of matrix metalloproteinases (MMPs). The formation of metastatic tissue in bones involves disrupting the balance of the bone remodeling process. The study delves into the three generations of bisphosphonates, elucidating their structural differences and mechanisms of action. First-generation bisphosphonates, such as etidronate and clodronate, lack nitrogen and interfere with cellular processes. Second-generation bisphosphonates, including alendronate and pamidronate, bind to nitrogen and inhibit farnesyl pyrophosphate synthase (FPPS) in the mevalonate pathway. Third-generation bisphosphonates like risedronate and zoledronate have a heterogeneous nitrogenous chain, enhancing anti-resorptive activity. Denosumab's distinct pharmacokinetics and potential risks upon discontinuation are discussed. The article emphasizes the need for clinicians to be vigilant about potential adverse effects, especially kidney toxicity with bisphosphonates, and to tailor treatment based on individual patient characteristics.